Root fragment weight and carbohydrate dynamics of two weedy thistles Cirsium arvense (L.) Scop. and Sonchus arvensis L. during sprouting - Marian Malte Weigel; Sabine Andert; Manuela Alt; Kirsten Weiß; Jürgen Müller; Bärbel Gerowitt (PeerJ)
Understanding the carbohydrate dynamics of sprouting Cirsium arvense (L.) Scop. and Sonchus arvensis L. ramets can assist in optimizing perennial weed management. However, detailed knowledge about general reserve dynamics, minimum values in reserves (compensation point) and different reserve determination methods remains sparse. We present novel insights into reserve dynamics, which are especially lacking for S. arvensis. We uniquely compare root weight changes as a proxy for carbohydrates with direct carbohydrate concentration measurements using high-performance liquid chromatography (HPLC). In a greenhouse study, ramets of two sizes (20 and 10 cm) were planted in pots. Subsequent creeping roots of sprouted plants were destructively harvested and analyzed for carbohydrates 12 times between planting and flowering. Efficiency in storing carbohydrates and the replenishing rate of root weight and carbohydrates was much higher in S. arvensis than in C. arvense. Thus, our study urges to evaluate perennial weed species individually when investigating root reserves. Determining root reserves by either using root weight changes as a proxy for carbohydrates or directly measuring carbohydrate concentrations by HPLC differed in the minimum values of reserves referred to as compensation points. For both species, these minimum values occurred earlier based on root weight than based on carbohydrate concentrations. Cutting ramets into 20 or 10 cm sizes did not significantly affect carbohydrate concentration or root weight changes for both species. We conclude that any practical applications targeting perennial weeds by fragmenting roots into small ramets through belowground mechanical control must be evaluated for trade-offs in soil structure, soil erosion, and energy consumption.